Pemanfaatan Microsoft Sway dan Microsoft Form Sebagai Media Pembelajaran Interaktif Pendidikan Agama Islam - Ari Priyono; Subar Junanto (Universitas Muhammadiyah Ponorogo, 2022)
The purpose of this study is to explain how to use the Microsoft Sway and Microsoft Form programs in history education and how to create interactive Islamic Religious Education media that can be accessed via a link. One of the challenges of learning Islamic religious education at this time during this pandemic is that the online learning materials used are less attractive so that it makes students less interested in using learning materials made by the teacher. In addition, students must download an application to access the media sent and must have a communication device with high mobile specifications to be able to open learning materials sent by the teacher. Students can quickly open Islamic Religious Education teaching materials using the Microsoft Sway and Microsoft Forms applications. Students can easily access Islamic Religious Education learning materials by clicking on links sent by teachers using the Microsoft Sway and Microsoft Forms applications, and teachers can use the Microsoft Sway application. to add media in the form of text, audio, video, animation, and quizzes in one link. This study uses a qualitative methodology. Microsoft Office 365 provides tools including Microsoft Sway and Microsoft Forms, according to the research findings. Teachers can produce interactive media in Islamic Religious Education creative learning using Microsoft Sway and Microsoft Forms without having to download certain software because these programs can be accessed online and have larger storage than Google Drive, so there's no need to worry while watching videos.